Evaluation of Hybrid Classroom Implementation in Room A101 - Ilham Alifudin; Hery Irwan (Institut Teknologi Dirgantara Adisutjipto, 2026)
The rapid development of information and communication technology (ICT) has accelerated the adoption of blended learning in higher education, combining traditional classroom instruction with online participation. To support this approach, universities require hybrid classroom systems that allow synchronous interaction between on-site and remote students. This study presents the design and implementation of a hybrid classroom in Room A101 using affordable and easily accessible devices. The system was built with a webcam connected to a mini PC and monitor, a wireless clip-on microphone integrated with the lecturer’s laptop, a projector supported by an HDMI switcher, and a stable internet connection. Implementation followed five stages: needs analysis, system design, installation, workflow, and evaluation. Technical testing covered video, audio, speaker performance, and internet stability, while user surveys captured perceptions of effectiveness. Results showed the system delivered acceptable 720p video, clear audio, and stable connectivity. Survey feedback indicated satisfaction levels of 82% for video, 88% for audio, 75% for speaker performance, and 84% overall. These findings confirm that low-cost hybrid classroom solutions can enhance flexibility, inclusivity, and accessibility in higher education, while remaining practical and replicable in similar institutional contexts.